MEDIA PEMBELAJARAN PERMAINAN MONOPOLI BIOLOGI MATERI KLASIFIKASI MAKHLUK HIDUP UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA SMP - Nurmiati Nurmiati; Zulkarnain Gazali (Bioscientist : Jurnal Ilmiah Biologi, 2018)
This study aims to determine the application of biology monopoly learning media on the material classification of living things in increasing motivation to learn junior high school students. This study uses a descriptive quantitative research approach that is oriented towards measuring student learning motivation. Data analysis techniques using motivation scores. Data collection techniques using student learning motivation questionnaire. The samples in this study were 64 grade 7 students of SMPN 14 and SMPN 17 Mataram taken using purposive sampling technique. Based on the results of the study it can be concluded that, biology monopoly media can build student motivation on aspects of interest in learning, independence in answering questions and the courage to express opinions.